Viticulture and wine tourism in Ukraine, the art of sommelier in times of war - Svidlo, K.; Bogdan, N.; Piddubna, L.; Tsymbal, B. M.; Ilienko, O.; Цимбал, Б. М. (Одеський национальний технологічний університет, 2025)
Ukraine is considered a European country with a developed grape growing and wine producing complex that produces a variety of wine products. However, our wine products are progressing slowly in European and global markets due to a number of objective political and economic reasons, including: the military conflict that has lasted for the past three years, insufficient funding for winemaking from the state, a reduction in vineyard area, the absence of tax benefits, high excise rates, and volumes of wine material production. Despite this, the development of ethnotourism significantly affects the level of socio-economic development of winemaking regions and the country as a whole, and is an important component of Ukraine's agro-industrial complex. Among the many benefits that ethnotourism brings to wine producers, the emergence of tourists (wine consumers) having an affinity for a specific type of wine produced in a particular place deserves special attention. This contributes to the growth of wine sales and, accordingly, to the increase in producers' income, provides an opportunity for direct contact between tourists and producers, and allows for the gathering of important information from tourists regarding the evaluation of the offered wine. Treating guests with national drinks, mainly wine, is an element of hospitality in almost all peoples of the world. Wine specialists and tourism business organizers are united by the fact that wine is an art that can rightfully be considered cultural heritage and must be preserved for future generations. Support measures for the development of ethno-tourism in various regions of Ukraine have been considered. Based on the studied materi3жal, an evaluation of the achieved results has been conducted, and recommendations have been provided to improve the effectiveness of entrepreneurship through the implementation of wine tours and the use of sommelier art to ensure the further development of this business (development of quality educational programmes for training specialists, etc.). The promotion of Ukrainian wine products in global markets needs to be stimulated through various methods, including wine tours that will broaden the understanding of Ukrainian wine products for both domestic and foreign tourists. Ethnotourism as an innovation in tourism and the hospitality industry can become an additional source of income for Ukraine's budget.
Keywords: viticulture; winemaking; ethnotourism; art; cultural heritage; sommelier